Gambaran Persepsi Remaja Tentang Seks Pranikah di Daerah Istimewa Yogyakarta - Hartanto, Dwi; Zulaicha, Endang (Universitas Muhammadiyah Surakarta, 2017)
Adolescence is a period of transition or the transition from childhood to adulthood experiencing all aspects of the development or function to enter adulthood. Courtship behavior is usually accompanied by a pattern of sexual behavior ranging from kissing, making out, until intercourse. Various factors affect the behavior of one due to the perception that teens have sex is a way of expressing love, so for the sake of love, someone to give up a sexual relationship with a boyfriend before marriage, environmental factors, promiscuity, lack of parental guidance especially religion both at home and at school. This study aims Knowing perceptions about premarital sex in adolescents in the village of Sleman Yogyakarta Tambaklelo. This study is a descriptive study with a cross-sectional approach. The samples were 27 teenagers in the village of Sleman Tambaklelo. The technique of collecting data using questionnaires. While using univariate data analysis techniques. The results showed that : ( 1 ) Perception of understanding adolescent premarital sexual behavior in adolescents in the village of Sleman Yogyakarta Tempel Tambaklelo mostly bad, ( 2 ) adolescent perceptions about the forms of premarital sexual behavior in adolescents in the village of Sleman Yogyakarta Tambaklelo Paste operation between perception of good and bad, ( 3 ) adolescent perceptions about premarital sexual deviant behavior in adolescents in the village of Sleman Yogyakarta Tempel Tambaklelo mostly good.